The Banū Yahrāsan, Political and Sacred Leaders in Ibāḍī Djerba - Prevost, Virginie (Al-Masāq, 2021)
From the beginning of the tenth century, a strong authority whose representatives belong to the Banū Yahrāsan asserts itself in Djerba. This exclusively masculine power is at once political and religious, it is hereditary, it marks a desire for appeasement in conflicts with schismatic groups and quickly gives a certain place, unfortunately difficult to evaluate, to collegiality. According to the written sources, the Banū Yahrāsan are at the origin of the foundation of the ḥalqa, determinant for the future of the Ibāḍī Maghreb, and have left a strong imprint that survives until today in the sacred geography of the island. The writings of Sulaymān al-Ḥīlātī show how this golden age was still captivating the seventeenth-century Ibāḍīs by inviting them to gather in many buildings, mosques or mausoleums, which perpetuate to this day the memory of the Banū Yahrāsan in Djerba.
Keywords: Ḥīlātī al-Ğarbī, Sulaymān ibn Aḥmad al- (16..-1688)

Les Sept Dormants dans le Sud tunisien : de la légende au culte vivant - Prevost, Virginie (Revue de l'histoire des religions, 2020)

Ilyās al-Hawwārī, homme de bien ibadite du XVIIe siècle, savant, faiseur de miracles - Prevost, Virginie (جزيرة جربة عبر التاريخ: من المحليّة إلى العالميّة | L'île de Djerba à travers l'histoire : Du local au mondial, 2025)
Parmi les savants ibadites djerbiens du XVIIe siècle, la personnalité d’Ilyās ibn Dāwud al-Hawwārī se distingue par la quantité de renseignements qui nous sont parvenus à son sujet, par le biais des sources écrites quasiment contemporaines ou plus tardives, mais aussi par la tradition orale locale qui l’associe à de nombreux monuments. Il est présenté comme le plus pieux des ʻazzāba par al-Ḥīlātī, qui décrit son rôle dans l’embellissement et l’agrandissement de la mosquée al-Shaykh de Houmt Souk et dans les visites de contrôle des mosquées de guet littorales. Il apparaît deux siècles plus tard, dans les mots d’Ibn Taʻārīt, comme un saint doté d’une puissante baraka, auteur d’impressionnants miracles, maître d’une zaouia réputée. Nous étudierons d’abord les tenants et aboutissants de cette étonnante transformation de l’image du notable djerbien, puis nous verrons dans quelle mesure son souvenir persiste aujourd’hui dans le patrimoine architectural de l’île. Cet itinéraire mémoriel, principalement centré autour du menzel qui a vu naître Ilyās al-Hawwārī, nous conduira des plus importantes mosquées ibadites aux plus modestes des maʻmūra.
Keywords: Biographies -- Djerba -- 17e siècle

Résistance et dévotion: Anciens sanctuaires ibadites de Djerba - Prevost, Virginie (British Institute for Libyan and Northern African Studies, 2023)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Majlis, Mosquée al- (Guellala, Djerba); Malāq, mosquée (Oued Zbib, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba); Yunus b. Taarit, mosquée (Fatou, Djerba)

Musulmans, juifs et chrétiens: l'heureuse cohabitation - Prevost, Virginie (Djerba à la carte, 2022)
Keywords: Tolérance religieuse -- Djerba

ثورة باغاي "969/358": آخر انتفاضة إباضية - Prevost, Virginie (دورية كان التاريخية, 2021)
Keywords: Révoltes -- Baghaya (Algérie)

Some observations on the cultural proximity between Tripolitania and the Island of Djerba - Prevost, Virginie (Tripolitania in the Roman Empire and Beyond, 2025)
This book provides an up-to-date account of the archaeology, history, economy, urbanism, art, and architecture of the North African region of Tripolitania during antiquity. The essays by international scholars outline current research and the most recent developments in the archaeology of this territory. The strong interdisciplinary character of the texts reflects the expertise of the different authors – from studies of the landscape and urban development, to funerary practices, architecture, military operations and food supply. This timely publication provides a much-needed new assessment of the evolution of this region throughout the Roman and Late Antique period.
Keywords: Relations -- Djerba -- Djebel Nefousa

Min Trībūlītānyā ilā Aṭrābulus : al-mashhad al-taʻmīrī khilāl al-ʻaṣr al-wasīṭ al-mutaqaddam bayn al-tawāṣul wa-l-taḥawwalāt من تريبوليتانيا إلى أطرابلس المشهد التعميري خلال العصر الوسيط المتقدّم بين التواصل والتحوّلات - Prevost, Virginie (Bulletin critique des Annales islamologiques, 2025)
Voici la première monographie publiée par le chercheur tunisien Hafed Abdouli, tirée en partie de sa thèse de doctorat consacrée à la Tripolitaine médiévale, défendue à Tunis en 2011 sous la direction de Faouzi Mahfoudh. L’ouvrage, préfacé par Ahmed M’Charek, constitue le premier volume d’une nouvelle collection des éditions Brill, Libya Islamica, et s’inscrit dans un intéressant programme de recherches dirigé par Aurélien Montel et Sébastien Garnier, Libmed, qui propose, sous la forme d’un s...
Keywords: Recension

PREVOST, Virginie. Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe-XIIIe siècle). London: Society for Libyan Studies Monograph 10, 2016, 231 páginas - Meouak, Mohamed (Miscelánea de estudios árabes y hebraicos, 2020)
Keywords: Recension

Entretien avec Virginie Prevost – Les mosquées ibadites - Somer, Florence (Les clés du Moyen-Orient, 2020)
Keywords: Monuments -- Djerba

Cyrille Aillet, L’archipel ibadite. Une histoire des marges du Maghreb médiéval - Prevost, Virginie (Bulletin critique des Annales islamologiques, 2023)
Voici enfin une monographie consacrée aux ibadites du Maghreb, depuis leur origine jusqu’au xve siècle, présentée en 2018 pour l’habilitation à diriger des recherches de Cyrille Aillet. Elle comprend onze chapitres, une chronologie, une vaste bibliographie et plusieurs index, notamment un très utile index des notions. Signalons, c’est assez peu courant, que l’index des personnes reprend aussi les noms des auteurs contemporains. Le livre retrace l’histoire des ibadites maghrébins et a pour obj...
Keywords: Recension

Ghardaïa, une île ? - Prevost, Virginie; Bouali-Messahel, Mounia (Traverser - Le déplacement en suspens, 2021)
Keywords: Urbanisme -- Mzab

Résistance et Dévotion. Anciens sanctuaires ibadites de Djerba - Chekhab-Abudaya, Mounia (Bulletin critique des Annales islamologiques, 2025)
Résistance et Dévotion : Anciens sanctuaires ibadites de Djerba, publié par Virginie Prevost, est le fruit d’un long travail commencé en 1996 et enrichi, depuis 2009, des clichés du photographe Axel Derriks. Cet ouvrage se présente comme une étude historique et architecturale minutieuse portant sur quarante-huit mosquées de l’île de Djerba, avec pour dessein de « conserver la mémoire des anciens lieux de culte de Djerba » (p. ix). Tout au long du volume, V. Prevost souligne de manière pertine...
Keywords: Architecture -- Djerba; Recension

Virginie Prevost, Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe–XIIIe siècle), Monograph 10, London: Society for Libyan Studies, 2016, 232 pp., ISBN 978 1 900971 41 6. - Gutiérrez, González Carmen (Der Islam, 2024)
Keywords: Recension

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition, by Paul M. Love - Prevost, Virginie (The English Historical Review, 2020)
This interesting and concise book finds its origin in Paul Love’s doctoral thesis defended in 2016 at the University of Michigan. It presents an innovative study of medieval Ibadi North-African Siyar. In the Maghrib, Siyar are books containing anecdotal and biographical information about individuals, playing the role of chronicle-style history; they function as prosopographies, collective biographies in which stories about individual members come together to form the biography of the community, constructing a North-African Ibadi tradition (p. xx). Love’s book tells the story of the compilation, adaptation and circulation of that prosopographical corpus through five scholars’ works. The pioneer is Abû Zakariyyâ’ al-Wârjalânî who provided Ibadi scholars of the second part of the eleventh century with a cohesive narrative of their history, when the community was suffering an ongoing numerical decline; he chose to write in the Arabic language at a time when use of the Berber language was also in decline. The author then studies the works of al-Wisyânî, al-Darjînî and al-Barrâdî. The last Ibadi scholar is al-Shammâkhî (d. 1522), who compiled all of the biographies of his predecessors into one collection and brought that medieval tradition of Ibadi prosopography to a close.
Keywords: Recension

Table ronde : Ghardaïa et la tradition moderne - Prevost, Virginie; Bouali-Messahel, Mounia; Bendimerad, Sabri (Traverser - Le déplacement en suspens, 2021)
Keywords: Urbanisme -- Mzab

Quelques remarques sur la diffusion du minaret-escalier et son lien avec les ibadites - Prevost, Virginie (Connected Stories: Contacts, Traditions and Transmissions in Premodern Mediterranean Islam, 2022)
Keywords: Archéologie -- Djerba

De la bsīsa pour les djinns… Les offrandes alimentaires dans le culte populaire à Djerba - Prevost, Virginie (Traditions alimentaires, nourritures quotidiennes et mets festifs dans le domaine berbère. Nouvelles recherches à la lumière des sources écrites et orales, 2025)
Keywords: Moeurs et coutumes -- Djerba